Synthesis of 5-Chloro-2-(4-tetradecanoyloxybenzylidenamino)benzoxazole - Ha, Sie-Tiong; Foo, Kok-Leei; Sreehari Sastry, S. (Asian Journal of Chemistry, 2012)
A new compound, 5-chloro-2-(4-tetradecanoyloxybenzylideneamino)benzoxazole was synthesized and characterized by IR, NMR and MS analysis.